Improvement The Fertility of Sandy Soil Amended using Bagasse and Different Type of Soil to The Yield of Shallot. Issue 1 (1st February 2022) - Fibrianty; Ma'as, A; Hanudin, E; Sudira, P
Abstract: The sandy soil in Samas Beach, Yogyakarta is characterized by the dominance of sand fraction, high leaching of nutrient, and high soil temperature. Shallot cultivation is possible in coastal sandy land through modification of microclimate and improvement of soil fertility. This study aimed to determine the effect of improving physical and chemical fertility of sandy soil amended by clay soil and bagasse to the yield of shallot. The study was conducted using Randomized Block Design with four treatments and four replications: Sandy Soil (S), Sandy soil + Bagasse (SB), Sandy soil + Latosol + Bagasse (SLB), Sandy Soil + Grumusol + Bagasse (SGB). Amendment increased moisture contents and decreased the permeability of sandy soil. SGB improved the highest water holding capacity, organic C and Total N of sandy soil. The highest yield of shallot reached at application of SLB and SGB, these treatments produced total dry weight of shallot, which were 19.63 and 23.85 g clump -1 . The combination of clay soil and bagasse was recommended as the amendment technology to improve the fertility of sandy soil.